Lab-scale design of two layers wood cellulose filter media to maximize life span for intake air filtration - Qian Yang (Nature Portfolio, 2021)
Abstract The requirement of continuous and stringent growth on filtration performance, including longer life span, higher overall efficiency, lower initial pressure drop and more cost effective, has still drove filter media manufactures to research and develop. One of the possible way to achieve these challenges, was to utilize a dual-channel head-box with two sets of pulp conveying system, which can produce filter media with bulky and gradient properties. In this study, three kinds of commercial cellulose were chosen to make two layers filtration media, analyzed the effect of fiber blend on physical properties and filtration performance. By fine-tune the slurry ratio of top layer, we made one single layer and two layers composition filter media, the thickness and air permeability of composition media were higher than single layer media. According to ISO 5011, filtration performance test has been done to compare single layer media with composition media, this composition gradient profiles that provided the life span 37.0% improvement to the terminal pressure drop during dust injecting, and the dust hold capacity improved 34.7%, the main contributor of dust hold capacity was decided by top layer, however, the overall efficiency was depended on wire side layer.